Chondroid Syringoma on Face - Min, Kyung Hee; Byun, Jin Hwan; Lim, Jung Soo; Lee, Hye Kyung; Lee, Won Mi; Joo, Jong Eun (Archives of craniofacial surgery, 2016)
Chondroid syringoma is a rare mixed tumor of the skin which is composed of both mesenchymal and epithelial cells. Its incidence at less than 0.1% and is frequently located on the head and neck. Chondroid syringoma is easily confused with epidermal cysts. Since malignant forms of chondroid syringoma have been reported, accurate and timely diagnosis is important for proper management. We report clinical and histological features of chondroid syringoma in 5 patients treated at our institution. In most of the cases, chondroid syringoma presented as a round, firm, nodular or cystic lesion that had well marginated heterogeneity in sonography. Clinically, all of the lesions were removed by simple excision. Microscopically, all five tumors were well circumscribed and consisted of epithelial, myoepithelial, and stromal components. The epithelial component formed tubules lined by one or more rows of eosinophilic epithelial cells. The outer layer of tubules appeared to be flattened myoepithelial cells. The stroma is myxoid and contained spindle shaped myoepithelial cells. We expect that the clinical, sonographic, and histological data from our report may help clinicians who are confronted with various kinds of analogous facial lesions to decide the most proper management for their patients.